Кодекс чести. Их было семеро: [роман] / Виктор Левашов - Левашов Виктор Владимирович (Кодекс чести, 2004)
Экземпляры: АБ (20190109) / Инвентарный номер: 41809 / Цена: 63.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л34 / ББК: 84(2Рос=Рус)6